HUBUNGAN PENDIDIKAN DAN PELATIHAN DENGAN INISIASI MENYUSU DINI PADA BIDAN DI PUSKESMAS SABUTUNG KABUPATEN PANGKEP - Sukma, Nurul; Nurhikmah (STIKES Pasapua Ambon, 2020)
Introduction : The puerperium is a critical time for both mother and baby because of the possibility of problems and complications during the puerperium, if not treated immediately effectively will endanger health. This study aims to determine the relationship of education and training with the implementation of early breastfeeding initiation in the Pabutung Health Center, Pangkep Regency. Method : This type of research is analytic research using cross sectional, the population in this study is 30 midwives, sampling using a total sampling of 30 midwives. Data were analyzed univariately and bivariately. Results: Univariate analysis, 100 injection acceptor KB (90.09%), and non- injection 11 (9.91). the results showed that there was a relationship between education (p = 0.009) and training (p = 0.017) with the implementation of early breastfeeding initiation where the p value <0.05. Conclusions: that there is a relationship between education and training with the implementation of early breastfeeding initiation at the Pabutung Health Center, Pangkep Regency. For midwives to further increase their knowledge of the implementation of early breastfeeding initiation and to midwives who have less knowledge in the implementation of early breastfeeding initiation so as to better enhance their understanding of the importance of carrying out early breastfeeding initiation.